Freedom is an endless meeting : democracy in American social movements - Polletta, Francesca (University of Chicago Press, 2002)
Freedom Is an Endless Meeting offers vivid portraits of American experiments in participatory democracy throughout the twentieth century. Drawing on meticulous research and more than one hundred interviews with activists, Francesca Polletta challenges the conventional wisdom that participatory democracy is worthy in purpose but unworkable in practice. Instead, she shows that social movements have often used bottom-up decision making as a powerful tool for political change. Polletta traces the history of democracy in early labor struggles and pre-World War II pacifism, in the.